Facilitating the Development of Intercultural Competence via Virtual Internationalization - Chen, Sibo (Frontiers in Communication, 2022)
This perspective article details a semester-long “internationalization at home” project that was piloted during Fall 2021 as part of emergency remote teaching and learning. By presenting the project’s components and overall student feedback, I demonstrate how virtual international collaboration contributes to the development of students' intercultural competence. Additionally, I emphasize that one-off faculty initiatives focused on collaborative transcultural learning will not suffice to embed this model into the local institutional matrix. Accordingly, the article concludes by advocating for stronger institutional support to leverage the promise of virtual internationalization.